Phule Gold (SSF 15-65): A new high oil and high oil yield variety of Safflower (Carthamus tinctirius L.), suitable for cultivation in India: Phule Gold (SSF 15-65): A new high oil and high oil yield variety of Safflower (Carthamus tinctirius L.), suitable for cultivation in India - L N TAGAD; D R MURUMKAR; S I TAMBE; S V KHADTARE; S K SHINDE (Journal of Oilseeds Research, 2023)
Safflower (Carthamus tinctorius L.) variety Phule gold (SSF-15-65) is derived by hybridization through pedigree selection method from a cross of Bhima x GMU 2724. It has semi-spreading habit with medium bold seeds. The variety is moderately tolerant to aphids and wilt. In various multilocation Coordinated trials conducted during 2017-18, 2018-19 and 2019-20 i. e. for 3 years, Phule gold (SSF-15-65) consistently recorded better performance over national check A1 and PBNS-12. Phule gold (SSF-15-65) recorded 24.80% higher oil yield over A1 and 17.10% over the check PBNS-12. The average oil content was 34.60 %. It was responsive to higher doses of fertiliser and late sown conditions. The variety was released and notified in 2020 for rainfed and irrigated safflower growing areas of the country (Maharashtra, Karnataka and Telegana state).